2019
DOI: 10.3892/wasj.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Role of p53 family isoforms in enhancing aggressiveness and chemoresistance in pancreatic cancer (Review)

Abstract: Pancreatic cancer remains one of the leading causes of cancer-related mortality worldwide. The role of p53 family isoforms in the pathogenesis of human cancer has been under the radar for decades, mainly due to the significant structural homology of p63 and p73 genes with the notorious p53 gene. Both p63 and p73 have two main isoforms, transactivating (TA) and deltaN (DN), each of which has been studied in normal and cancer cells. Although their role in cancer remains elusive and is tissue-specific, the manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 165 publications
(208 reference statements)
0
6
0
Order By: Relevance
“…TP53 has been known to be mutated in 70% of cases in pancreatic cancer, causing the loss of DNA-binding ability, which activates the transcription of genes [48]. The progression of malignant pancreatic cancer was found to be associated with the sustained expression of mutant TP53 [49]. From the previous study, R273H mutation of P53 in MiaPaca-2 pancreatic cancer cell lines have been found to play roles in increasing colony formation and proliferation, and resistance to drug [49].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TP53 has been known to be mutated in 70% of cases in pancreatic cancer, causing the loss of DNA-binding ability, which activates the transcription of genes [48]. The progression of malignant pancreatic cancer was found to be associated with the sustained expression of mutant TP53 [49]. From the previous study, R273H mutation of P53 in MiaPaca-2 pancreatic cancer cell lines have been found to play roles in increasing colony formation and proliferation, and resistance to drug [49].…”
Section: Discussionmentioning
confidence: 97%
“…The progression of malignant pancreatic cancer was found to be associated with the sustained expression of mutant TP53 [49]. From the previous study, R273H mutation of P53 in MiaPaca-2 pancreatic cancer cell lines have been found to play roles in increasing colony formation and proliferation, and resistance to drug [49]. A study on MO demonstrated that the hot water leaf extract of the plant revealed the antiproliferative effect in the lung cancer cell, A549, by the activation of P53, caspases, and PARP1 cleavage, which led to the apoptosis of the cancer cell [50].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the p53 gene and its isoforms have resulted in more aggressive cancers of all types with an earlier onset. Research revealed p53 to be mutated in 75% of pancreatic adenocarcinoma patients [64]. While considering this, our analysis revealed the value of HbA1 in disease-free individuals to be approximately 1050 tpm; about 10 tpm in patients with mutated p53, and about 30 tpm in patients with pancreatic cancer with no mutated p53 gene.…”
Section: Analysis Of the Oncoinformatic Parametersmentioning
confidence: 63%
“…In pancreatic cancer, the tumor protein p53 is mutated and accelerates the tumorigenesis in 75% of cases [57]. Therefore, p53 tumor protein was selected as a biomarker in this study.…”
Section: Quantification Of P53 Protein Levelsmentioning
confidence: 99%